Implementation of creative characters through the project to strengthen the pancasila student profile in the field of entrepreneurship at smpn dawarblandong - Srinarwati, Dwi Retnani; Widayanti, Dwi (Universitas Tanjungpura, 2025)
Indonesia's unemployment rate is expected to hit 7.99 million in February 2023. Strengthening the Profile of Pancasila Students is one way the Indonesian education system proposes to address this, with the goal of developing the next generation of creative and innovative thinkers. This study aims to provide an overview of the Pancasila Student Profile Strengthening Project's implementation of creative character development, character education, and character education through the program in the field of entrepreneurship at SMPN 2 Dawarblandong. A qualitative descriptive research methodology was employed in this study. Interviews, observation, recording, and questionnaires are some of the methods used in data collecting. The study's participants were the principal of SMPN 2 Dawarblandong, a teacher in the school's curriculum department, the supervisor of SMPN 2 Dawarblandong's Pancasila Student Profile Strengthening Project, and grade VII students. Triangulation of sources and methodologies is used to ensure the veracity of this data. Data gathering, data reduction, data presentation, and verification procedures are all used in data analysis, which is qualitative analysis. The findings showed that character education was being implemented at SMPN 2 Dawarblandong even prior to the creation of the Independent Curriculum, and that it recommenced following the adoption of the Ministry of Education and Culture for Research and Technology Number 162/M/2021 Decree. The Pancasila Student Profile Strengthening Project's co-curricular entrepreneurship-themed activities are one way that character education is put into practice. Two aspects of character